Matrix metalloproteinases and coronary artery diseases - Ikeda, Uichi (Clin Cardiol, 2006)
Matrix metalloproteinases (MMPs) play an important role in cardiovascular remodeling by degrading the extracellular matrix. Enhanced MMP expression has been detected in the atherosclerotic plaque, and activation of MMPs appears to be involved in the vulnerability of the plaque. Circulating MMP levels are elevated in patients with acute myocardial infarction and unstable angina. Increased MMP expression is also observed after coronary angioplasty, which is related to late loss index after the procedure. These observations suggest that MMP expression may be not only related to instability of the plaque, but also to the formation of restenotic lesions. The development of therapeutic drugs targeted specifically against MMPs may be useful in the prevention of atherosclerotic lesion development, plaque rupture, and restenosis.